NEW ADDITIONS OF BRYACEOUS MOSSES (MUSCI, BRYACEAE) TO THE ANTARCTIC FLORA (Twelfth Symposium on Polar Biology) - オチ, ハルミ; カンダ, ヒロシ; OCHI, Harumi; KANDA, Hiroshi (National Institute of Polar Research, 1991)
P(論文) Bryum pallescens SCHLEICH. ex SCHWAEGR. is recognized for the first time from the Peninsular site, Antarctica, based on a collection made by a U.S. botanist (NIPR 850409-002 ex NY). Furthermore, examining three duplicates named "Bryum algens CARD." from East Antarctica, it has been revealed that at least one of them (NIPR 870610-007, from Wilhelm II Land) belongs to Bryum pseudotriquetrum (HEDW.) GAERTN., MEYER et SCHERB., which is a new record to the region around the USSR base. departmental bulletin paper